PERSEPSI ORANG TUA SISWA SD TERHADAP PEMBELAJARAN PADA ERA NEW NORMAL DI KABUPATEN MELAWI - Waridah (Pusat Riset dan Inovasi Nasional, 2021)
This study aims to determine the perceptions of parents of elementary school (SD) students towards learning in the new normal era in Melawi Regency. Data collection in this study used an online questionnaire with the Google form application which was given to all parents of elementary school students in Melawi Regency as many as 31 people. This study uses mixed method which is a combination of quantitative and qualitative methods. The subjects of this study were 31 people. Data collection techniques used parental perception questionnaires, interviews, and documentation. The data analysis technique uses the Miles and Huberman model, namely data reduction, data presentation, and drawing conclusions. The results of this study obtained data that with regard to face-to-face learning in the New Normal era, the majority of parents agreed at 96.8%. While the rest stated disagree as much as 3.2%. Overall, based on parental responses regarding perceptions of the new normal era learning process, its advantages and convenience compared to online learning, it was obtained that an average of 87.1% of parents agreed and 12.9% of parents stated that they did not agree with the consideration that there were still concerns. against the pandemic that occurred, and the implementation of the shift process of learning hours which was felt to be useless because it was too short. In addition, the parents' perception of their participation in children's learning assistance was on average 59.37% in the frequent category, 36.12% in the occasional category, and 4.51% in the never category.